PENGARUH IKLIM KESELAMATAN, SISTEM MANAJEMEN KESELAMATAN, DAN PERILAKU KESELAMATAN TERHADAP BUDAYA KESELAMATAN STAF KLINIS DI RS GUNUNG MARIA - Frankly Oktavian Palendeng; Innocentius Bernarto (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Abstract: This study aims to 1) analyze and examine the effect of safety climate on safety culture, 2) analyze and examine the effect of safety climate on safety behavior, 3) analyze and examine the effect of safety management systems on safety culture, 4) analyze and test the infulence of systems safety management on safety climate, 5) analyze and test the influence of safety management systems on safety behavior, and 6) analyze and test the influence of safety behavior on safety culture. Data were collected through questionnaires which were distributed to respondents who were clinical staff at the Gunung Maria Hospital using a saturated sampling technique. Data analysis using partial least squares – structural equation modeling (PLS-SEM) using the SmartPls program. This study found that safety climate, safety management system, and safety behavior have a positive effect on safety culture. Safety management systems also have a positive influence on safety climate and safety behavior. However, it is different from the safety climate which has no effect on safety behavior.